PENINGKATAN KUALITAS DAN KEAMANAN GULA AREN DI LOMBOK UTARA - Wijaya, Fransisca; Elfriede, Dwining Putri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
North Lombok is the only underdeveloped district in NTB. Menggala Village in North Lombok is strategically located close to Mataram city center and Gili Trawangan harbor. Menggala Village has the largest palm sugar-producing center in North Lombok. This potential has not been able to increase the economy of palm sugar craftsmen. This is due to the processing of palm sugar which is still very simple both in terms of production and packaging. In addition, marketing that has not been widespread is also an obstacle. For this reason, the objectives of this activity include increasing the knowledge and understanding of palm sugar craftsmen in making high-quality and safe products, increasing understanding of labels and packaging, improving product marketing strategies into superior local products, and knowing the nutritional value contained in products. This activity consists of FGD, training, and advanced mentoring stage. The FGD results show that palm sugar farmers need training on GMP, packaging, and business development. The results of this training were able to significantly increase the partners' knowledge. Partner production facilities become more feasible and hygienic. The results of the product analysis meet the quality requirements of SNI. However, partners still need to develop their business through local marketing in collaboration with gift centers and actively participate in MSME bazaars or exhibitions in the local area.